Determinants of Micro Credit Performance in Microfinances in Kenya - Munguti, Joe Mulili (My University, 2013)
Efficient debt management determines the cash flow and the success of the day-to-day operations of the business. Poor credit management leads to late payment to creditors and other stakeholders in the supply chain. This study focused on the determinants of micro credit performane in kenya. The objective of this study was to establish factors that determine micro credit performance in Kenya.The researcher surveyed loan accounts of a micro finace institution. The researcher took micro loan accounts at Small and Micro Enterprises programme- Deposit Taking Microfinance (SMEP- DTM) at Machakos branch in Machakos County. This study focused on all types of loans by the micro finance for the period running from 1ST July 2009 to 30 June 2012. During this period the microfinance advanced a total of 7000 loans. The researcher used stratified sampling to get a sample size of 180 borrowers. The data was gathered using questionnaires and analyzed using Logit model in the Statistical Package for Social Sciences (SPSS). Determinants of micro credit performance include the age of the borrower, whether the client had been a customer or not , whether is a man or woman, the level of education and others. Earlier studies indicate women borrowers were better repayers than men. The level of education improves repayment rate for which the reaseacher does not expect it to change for micro credit perfomance in Kenya. The study found the default rate to be 46.36 per cent. This percentage confirms findings of the public development finance institutions which recorded similar trends. The NEF Mbewu Fund, which is aimed at developing small businesses, found that 67 per cent of loan repayments were not paid back on time during the 2009 financial year. Timm (2011) noted the default rate as a “sickness” affecting South African SMEs and the findings of this research validate Tinam‟s concerns about small business‟s poor payment rate.